The splendor of Roman wall painting - Pappalardo, Umberto 1949- (J. Paul Getty Museum, 2009)
"Visitors to the former residences of wealthy citizens of ancient Rome cannot help but be astonished by their grand architecture and enchanting wall paintings, still vibrant with cinnabar reds, golden yellows, and deep greens. The beauty and intricacy of these ancient frescoes are showcased in the sumptuous volume Domus: Wall Painting in the Roman House, published by the J. Paul Getty Museum in 2004 and now available in this abridged and affordable edition ... Following an introduction to the Roman domestic ideal that inspired these wall decorations and a discussion of the evolution in painting styles, the author conducts a tour of twenty-eight houses in Pompeii, Herculaneum, Oplontis, and the city of Rome. Here are painted scenes - rich with fabulous details of illusionistic architecture, Irish gardens, exotic animals, and erotic adventures - impressive in their display of technical mastery and enduring in their visual impact"--BOOK JACKET
Keywords: Mural painting and decoration, Roman -- Italy; Interior decoration -- Rome; Wandmalerei; Italien; Rom; Römisches Reich; Bildband